Seeing is believing. The bicoid morphogen gradient matures. - Ephrussi, A.; St. Johnston, D. (Cell, 2004)
Although Cell has a long history of publishing some of the most significant advances in developmental biology, the back to back papers by Driever and Nüsslein-Volhard on the role of the Bicoid gradient in patterning the Drosophila embryo stand out as the first molecular demonstration of two of the longest standing concepts of the field, namely localized cytoplasmic determinants and morphogen gradients. Here we discuss the impact of this ground-breaking work and review recent results on bicoid mRNA localization and the dual role of Bicoid as a transcription and translation factor.